#TITLE_ALTERNATIVE# - Nyoman Widana Negara (NIM S2888813), I
ABSTRACT: Selection of suitable methods to gather speed and volume information is needed to establish speed and volume relationships. The video camera survey method which was used in the present study was shown to have several advantages, in sample size and accuracy of timing in comparison with registration plate matching. The study obtained significant speed and volume relationships on three heavy trafficked road links in and near Bandung. Three macroscopic speed-volume models (linear, Greenshields and Greenberg) were applied at all sites. It was found that Greenbergs model generally gave better results than the others. Greenbergs model was also used to investigate the effect of using shorter (5 minute) and longer (10 minute) time intervals for analysis. Passenger car unit (pcu) values for the links were estimated using multiple linear regression for five vehicle classes: car, opelet, bus, truck and motorcycle. Simple regression and correlation were applied to investigate the effect of opposing volume on average speed, the results of which were inconclusive. The effects of side friction were also investigated, as expressed by individual and combined effects of parked vehicles, unmotorised vehicles and pedestrian activity on the roadway. High side friction was generally associated with lower speed, though the relationship was sometimes complex and its nature varied from site to site.